Identification Of Physiotherapy Student Fitness At Poltekkes Kemenkes Surakarta - Herdianty Kusuma Handari; Mei Kusumaningtyas (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: The convenience provided by technology makes a person tend to reduce physical activity. In a long time it will certainly have an impact on one's fitness. This will also affect adolescents to young adults, where the average circle is students in college. Fitness is very important to support daily activities, without fitness someone will easily experience fatigue. Currently, students tend to do less physical activity because they lie too much or are sedentary as a result of technological advances. As a physiotherapy student who will treat patients later, fitness needs to be maintained since in the college. So far, fitness identification has never been done for students in health institutions, especially in physiotherapy students in the Poltekkes Kemenkes Surakarta, so this study aims to determine the fitness condition of physiotherapy students. Methods: this research is a descriptive study by measuring 8 fitness components namely flexibility, balance, strength, explosive power, speed, agility, coordination and endurance in 226 physiotherapy students and the data analized descriptively using Ms. Excel. Results: Based on the measurement results, it was found that flexibility, balance and strength were included in the good category, explosive power, agility and coordination were in the very poor category, speed and endurance were in the excellent category. The physiotherapy student fitness index shows an average value of 3.125, which means that student fitness is included in the fair category. Conclusion: there is efforts should be made to maintain and improve the fitness of physiotherapy students in the Poltekkes Kemenkes Surakarta.